Germination patterns along a salinity gradient of closely-related halophytes in sympatry. (5th January 2022) - Moreno, Joaquín; Terrones, Alejandro; Juan, Ana
Abstract: Sympatric closely-related species co-occur within heterogeneous environments by occupying separate ecological niches as result of adaptive differentiation. Soil salinity is one of the most relevant drivers leading plant zonation in salt marshes, where germination is a critical stage in the life cycle of many halophytes. Salinity influence on germination patterns was evaluated for six sympatric Limonium species ( L. admirable, L. caesium, L. cossonianum, L. delicatulum, L. supinum and L. tobarrense ), which grow under arid environmental conditions in an inland salt marsh from the southeastern Spain. Experiments were conducted to determine the effects of different salinities (0–6% NaCl) on seed germination under 12 h in light at 25 °C and for 12 h in dark at 20 °C. Best seed germination was obtained under non-saline conditions, and germination was delayed and significantly reduced by increasing the salinity levels for all the studied taxa. The germination variables related to final germination percentage, mean time to germination and recovery were directly influenced by salinity. Seeds recovered their germination capacity after transferring the seeds from saline solutions to distilled water, especially those seeds previously treated under high salinity conditions. Our results suggest that the successful establishment of Limonium communities depends on the germination strategy which implies a rapid germination velocity when the soil salinity decreases. Two different germination syndromes based on germination percentage and germination recovery have been found. Hence, these germination strategies would favour the adaptation of different Limonium species under favorable conditions, shaping the plant asssembly within the saline habitat. Graphical abstract: Image 1 Highlights: The successful establishment of Limonium communities depends on the rapid germination velocity when the soil salinity decreases. Two different germination syndromes based on germination percentage and germination recovery appear on the Limonium morphotypes. Germination strategies favour the Limonium species adaptation under favorable conditions, establishing the ecological assembly.